Nilai Prognostik FLT3 Pada Pasien Leukemia Mieloid Akut - Hendra Asputra (Fakultas Kedokteran Universitas Riau, 2021)
Acute myeloid leukemia (AML) is a disease characterized by neoplastic transformation and abnormality of progenitor cells differentiation from myeloid cells. In AML there is a heterogeneous abnormality in hematopoietic progenitor cells, this abnormality has been identified and affects the balance between proliferation, survival and differentiation of body cells. Mutation of FMS-like tyrosin kinase 3 (FLT3) gene causes overexpression which is one of the most often found mechanism that has been identified could trigger genetic changes that can disturb intracellular signaling tissue in pathogenesis of leukemia. Besides being used as a diagnostic tool, FLT3 overexpression can also be used to assess the prognosis of AML.